2020
DOI: 10.1039/c9sc05532k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed intermolecular transthioetherification of aryl halides with thioethers and thioesters

Abstract: Functional group transfer reactions are an important synthetic tool in modern organic synthesis. Herein, we developed a new palladium-catalyzed intermolecular transthioetherification reaction of aryl halides with thioethers and thioesters. The synthetic utility and practicality of this catalytic protocol are demonstrated in a wide range of successful transformations (>70 examples). This catalytic protocol is applicable in carbonylative coupling processes as well, and the first example of carbonylative methylth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…As a seminal work, Wu and co-workers developed a new palladium-catalyzed intermolecular transthioetherification reaction of aryl halides (88) with thioethers and thioesters (89) to afford a broad range of the corresponding thiomethylation and carbonylative thiomethylation products (>70 examples) in good to excellent yields with satisfying functional group compatibility (Scheme 34). 58 Moreover, this method provided the first example of carbonylative methylthioesterification of aryl halides under the similar reaction conditions. The scope of this system showed that both electron-poor and -rich substrates could be converted into the desired products with alkyl sulfides as the sulfur source.…”
Section: Sulfenylation Of Aryl Halidesmentioning
confidence: 94%
“…As a seminal work, Wu and co-workers developed a new palladium-catalyzed intermolecular transthioetherification reaction of aryl halides (88) with thioethers and thioesters (89) to afford a broad range of the corresponding thiomethylation and carbonylative thiomethylation products (>70 examples) in good to excellent yields with satisfying functional group compatibility (Scheme 34). 58 Moreover, this method provided the first example of carbonylative methylthioesterification of aryl halides under the similar reaction conditions. The scope of this system showed that both electron-poor and -rich substrates could be converted into the desired products with alkyl sulfides as the sulfur source.…”
Section: Sulfenylation Of Aryl Halidesmentioning
confidence: 94%
“…reported the synthesis of methylthio‐esters from thioethers and thioesters following trans‐thioetherification of aryl halides under homogeneous palladium chloride, Xantphos ligand at 20 bar CO gas pressure (Scheme 1). [10] …”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Jiang and co-workers reported a dicarbonylation of amine and aryl borates using α-ketothioester as a stable 1,2-dicarbonyl reagent [ 16 ] ( Scheme 1 , B). Recently, we applied S -methyl butanethioate in a Pd-catalyzed transthioetherification or transthioesterification of aryl halides for the synthesis of thioethers and thioesters [ 17 ] ( Scheme 1 , C). In addition, we also used this reagent to trap alkylcopper(I) intermediates and to form C−S bonds [ 18 ].…”
Section: Introductionmentioning
confidence: 99%